2013
DOI: 10.1039/c2cc37428e
|View full text |Cite
|
Sign up to set email alerts
|

A family of simple benzene 1,3,5-tricarboxamide (BTA) aromatic carboxylic acid hydrogels

Abstract: We present the characterisation of a hydrogel forming family of benzene 1,3,5-tricarboxamide (BTA) aromatic carboxylic acid derivatives. The simple, easy to synthesise compounds presented here exhibit consistent gel formation at low concentrations through the use of a pH trigger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 64 publications
0
52
0
Order By: Relevance
“…This is best described using pH and ionic strength dependent state diagrams, which are well known for self-assembled natural spherical or filamentous viruses. 174,[314][315][316][317] Note that pH-dependent self-assembly using synthetic small molecular weight building blocks was already reported earlier by the groups of van Esch, 318 Hartgerink, 319 Goldberger, 306 and others, [320][321][322][323] as well as the ionic strength dependent supramolecular polymerization processes in the Meijer and Rivera groups. [324][325][326][327][328] Importantly, repulsive contributions in supramolecular systems and polymers can also be based on steric constraints, as reported by Stupp, 329 Lee, 330 Hedrick, 331 Fernandez, Schacher, 332 and Besenius.…”
mentioning
confidence: 84%
“…This is best described using pH and ionic strength dependent state diagrams, which are well known for self-assembled natural spherical or filamentous viruses. 174,[314][315][316][317] Note that pH-dependent self-assembly using synthetic small molecular weight building blocks was already reported earlier by the groups of van Esch, 318 Hartgerink, 319 Goldberger, 306 and others, [320][321][322][323] as well as the ionic strength dependent supramolecular polymerization processes in the Meijer and Rivera groups. [324][325][326][327][328] Importantly, repulsive contributions in supramolecular systems and polymers can also be based on steric constraints, as reported by Stupp, 329 Lee, 330 Hedrick, 331 Fernandez, Schacher, 332 and Besenius.…”
mentioning
confidence: 84%
“…8,12 Given the fibrous nature of the crystals formed by each of the compounds, the gelation abilities of 1-5 in a variety of solvent conditions were also investigated. Gel formation was not observed under any conditions investigated for the ester derivatives 2 and 4, which generally formed crystalline or micro-crystalline solids upon precipitation.…”
Section: Gelation Studiesmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Numerous studies into the self-assembly properties of BTAderived structures and their supramolecular polymerization have been carried out, especially by Palmans, Meijer and coworkers. 8,9,10,11 We have recently focused our efforts on the use of BTA-based ligands in the generation of functional soft materials such as lanthanide and transition metal ion based metallogels. 12 We have also employed the BTA unit in the generation of tripodal anion receptors 13 and N-methyl BTA derived platforms for the formation of anion-directed selfassembled cages and self-sorting assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Besenius and coworkers mixed the oppositely charged dendritic peptide amphiphiles in a 1:1 ratio to supramolecular copolymers through a combination of Coulomb attractive forces and hydrogen‐bonding interactions . Lloyd and coworkers reported that a family of aromatic carboxylic acid benzene 1,3,5‐tricarboxamide (BTA) modifications showed spontaneous nucleation and one‐dimensional growth resulting from the molecules stacking into fibers through π ‐stacking interactions and amide–amide hydrogen bonding …”
Section: Introductionmentioning
confidence: 99%